2010
DOI: 10.1159/000314644
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes toward Ethical and Social Issues Surrounding the Expansion of Newborn Screening Using New Technologies

Abstract: Aims: This study assessed parent knowledge of newborn screening (NBS) and parent attitudes toward NBS for untreatable conditions, NBS for late-onset disorders and informed consent in NBS. Methods: Seventeen qualitative focus groups were held in Alaska, California, Hawaii, and Washington with mothers of children 10 years old or younger. Results: Most participants did not recall receiving information about NBS, and all wanted this information prenatally. In addition, most felt that the current system of ‘informe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 75 publications
8
49
0
Order By: Relevance
“…Participants' strong acceptance of NBS for several different conditions, including fatal neurological disorders, is significant and in line with other studies across the United States and European Union (Brunger et al, 2000;Lipstein et al, 2010;Plass et al, 2010;Hasegawa et al, 2011). Together, these findings suggest that Wilson and Junger's screening principles should be updated to include a broader concept of benefit than medical treatment (Hasegawa et al, 2011) and also challenge critics of NBS expansion who argue that a disorder should only be included in a screening panel if an effective treatment exists (Botkin et al, 2006). While our respondents overwhelmingly indicated that they would be interested in newborn testing to be prepared for the birth of a child with a genetic disorder, a large majority also agreed that they would use information from newborn testing for fatal neurological disorders in their future reproductive decisions.…”
supporting
confidence: 79%
“…Participants' strong acceptance of NBS for several different conditions, including fatal neurological disorders, is significant and in line with other studies across the United States and European Union (Brunger et al, 2000;Lipstein et al, 2010;Plass et al, 2010;Hasegawa et al, 2011). Together, these findings suggest that Wilson and Junger's screening principles should be updated to include a broader concept of benefit than medical treatment (Hasegawa et al, 2011) and also challenge critics of NBS expansion who argue that a disorder should only be included in a screening panel if an effective treatment exists (Botkin et al, 2006). While our respondents overwhelmingly indicated that they would be interested in newborn testing to be prepared for the birth of a child with a genetic disorder, a large majority also agreed that they would use information from newborn testing for fatal neurological disorders in their future reproductive decisions.…”
supporting
confidence: 79%
“…65 The review also suggested that there could be differences in parents' and health professionals' views regarding the timing of information provision and consent models. 91 As this may explain one of the barriers to effective NBS, it is important that future research examines this. However, one of the issues that this review highlights is the difficulty of comparing midwives' (or health professionals') views with those of parents if the research is conducted at different time points, as changes in screening could account for differences in opinion.…”
Section: Discussionmentioning
confidence: 99%
“…being included in the review, 8,12,14,15,17,19,20,25,26,[28][29][30]33, covering NBS in a number of different countries: England (n = 11 8,14,25,62,66,70,72,[78][79][80]83 ), Wales (n = 2 85,86 ), France (n = 1 89 ), Germany (n = 1 15 ), the Netherlands (n = 1 29 ), USA (n = 20 17,19,26,30,33,61,63,64,71,[74][75][76]81,82,84,87,88,90,91,93 ), Canada (n = 4 12,65,…”
Section: Theories Of Informed Consent: Developing An Analytical Framementioning
confidence: 99%
“…23,24 To date, the literature concerning consent and newborn screening has generally focused on attitudes toward consent policy. 7,[25][26][27][28][29] Although this is revealing, occasionally showing conflicting attitudes toward the need for consent, 6,30,31 there is a lack of descriptive research that depicts how the offer of NBS is made to parents, making it difficult to determine the experience of consent in practice. Understanding the experiences of those actually involved in the consent process may provide valuable descriptive information for NBS programs and providers.…”
Section: Introductionmentioning
confidence: 99%